The TOR signaling pathway regulates starvation-induced pseudouridylation of yeast U2 snRNA - Wu, Guowei (RNA, 2016)
Pseudouridine (Ψ) has been identified in various types of RNAs, including mRNA, rRNA, tRNA, snRNA, and many other noncoding RNAs. We have previously shown that RNA pseudouridylation, like DNA and protein modifications, can be induced by stress. For instance, growing yeast cells to saturation induces the formation of Ψ93 in U2 snRNA. Here, we further investigate this inducible RNA modification. We show that switching yeast cells from nutrient-rich medium to different nutrient-deprived media (including water) results in the formation of Ψ93 in U2 snRNA. Using gene deletion/conditional depletion as well as rapamycin treatment, we further show that the TOR signaling pathway, which controls cell entry into stationary phase, regulates Ψ93 formation. The RAS/cAMP signaling pathway, which parallels the TOR pathway, plays no role in this inducible modification.